The Relationship Between Mobile Marketing and Customer Perceptions in Jordanian Commercial Banks: The Electronic Quality as A Mediator Variable - Daoud, Mohammad Khalaf; Alqudah, Derar; Al-Qeed, Marzouq; Al Qaied, Bader Ayed; Ahmad, Ahmad Y A Bani (International Journal of Membrane Science and Technology, 2023)
This study aims to investigate the factors influencing customer perceptions of Jordanian commercial banks, with a specific focus on the moderating role of electronic quality in mobile marketing. A comprehensive literature review was conducted, leading to the development of a research framework illustrating the research case. The theoretical foundation of this study is grounded in the concept of perceived attributes, which identifies five key factors affecting the rate of adoption. The empirical findings of this research, based on a sample of 400 respondents (N = 400), are presented. The analyses were performed using the statistical technique of Partial Least Squares Structural Equation Modeling (PLS-SEM). The reporting style adheres to the widely accepted practices in PLS-SEM analysis. The findings highlight a significant and robust relationship between mobile marketing and customer perceptions within the context of Jordanian commercial banks, particularly when electronic quality is employed as a moderator variable. Based on these results, we recommend that Jordanian commercial banks strategically integrate electronic quality into their digital marketing operations, with a specific emphasis on mobile marketing.